The Orce man: controversy, media and politics in Spanish human origins research - Carandell Baruzzi, Miquel (Cultural dynamics of science, 2021)
"The Orce Man controversy is a very long, complicated and harsh dispute among scientific colleagues (often from the same institution) over the taxonomic classification of a cranial fragment. The fossil was found in 1982 by three palaeontologists from the Institut de Paleontologia de Sabadell in Catalonia: Josep Gibert, Jordi Agustí and Salvador Moyà-Solà at a site called Venta Micena, near the small town of Orce, located in a very arid region of the province of Granada, Andalusia"--